Development and application of a whole genome amplicon sequencing method for infectious salmon anemia virus (ISAV) - Spilsberg, Bjørn; Leithaug, Magnus; Christiansen, Debes Hammershaimb; Dahl, Maria Marjunardóttir; Petersen, Petra Elisabeth; Lagesen, Karin; Fiskebeck, Eve M. L. Z.; Moldal, Torfinn; Boye, Mette (Frontiers in Microbiology, 2024)
Infectious salmon anemia (ISA) is an infectious disease in farmed Atlantic salmon, Salmo salar, caused by the infectious salmon anemia virus (ISAV). ISAV belongs to the Orthomyxoviridae family. The disease is a serious condition that can lead to reduced fish welfare and high mortality. In this study we designed an amplicon based sequencing protocol for whole genome sequencing of ISAV. The method consist of eighty ISAV specific primers that cover 92% of the virus genome and was designed to be used on a Illumina MiSeq platform. The sequencing accuracy was investigated by comparing sequences with previously published Sanger sequences. The sequences obtained were nearly identical to those obtained by Sanger sequencing, thus demonstrating that sequences produced by this amplicon sequencing protocol had an acceptable accuracy. The amplicon based sequencing method was used to obtain whole genome sequence of 12 different ISAV isolates from a small local epidemic in the northern part of Norway. Analysis of the whole genome sequences revealed that segment reassortment had taken place between some of the isolates and could identify which segment that had been reassorted.